Nahua biocultural richness: an ethnoherpetological perspective - Miriam Itzel Linares-Rosas; Benigno Gómez; Elda Miriam Aldasoro-Maya; Alejandro Casas (BMC, 2021)
Abstract Background Mexico harbours one of the greatest biocultural diversities of the world, where multiple social and natural elements and systems form complex networks of interactions in which both culture and nature are mutually influenced. Biocultural states and processes are studied by ethnosciences, among them ethnoherpetology, which seeks understanding material and non-material expressions of the interactions between humans, amphibians, and reptiles. Herpetofauna has been part of the magic-religious world and source of goods for Mesoamerican cultures. This study aims to document and analyse the complex body of knowledge, beliefs, and practices on these vertebrates in the Nahua culture, the factors that have influenced progressive risk and loss of culture, habitat, and species, and the potential contribution of contemporary Nahua knowledge to biocultural conservation. Methods Through 15 workshops with children and young people, and 16 semi-structured interviews to people 27 to 74 years old, we documented the contemporary Nahua knowledge in the communities of Aticpac and Xaltepec in the Sierra Negra, Puebla, central Mexico. Biological and ecological knowledge, use, management practices, legends, and perceptions on herpetofauna were emphasised in the study. Results We obtained an ethnoherpetological checklist, grouping species into four general classificatory categories: kohuatl (serpents), kalatl (frogs and toads), ayotsi (turtles), and ketzo (lizards and salamanders), which included 21, 10, 1, and 11 ethnocategories respectively, based on the local Nahua knowledge of herpetofauna. Serpents, used as medicine, are the most culturally relevant. Due to perceptions of danger, beliefs, and actual snake bites, the main interaction with serpents is their elimination; however, some snakes are tolerated and maintained in captivity. The remaining species of local herpetofauna recorded are tolerated. Cultural aspects of reptiles and amphibians in the Nahua worldview were documented to influence the regulation of interactions of people with these vertebrates, but for younger generations, such aspects are less frequent or absent. Conclusions Interactions and cultural relationships between the Nahua people, amphibians and reptiles are complex, maintaining some aspects of the local worldview but also influenced by external factors and being constantly recreated and re-signified. Documenting and understanding the contemporary relations is essential to generate strategies in biocultural conservation of herpetofauna.